Are joint implementation and the clean development mechanism opportunities for forest sustainable management through carbon sequestration projects? - Mulongoy, K.J.; Smith, J.; Alirol, P.; Witthoeft-Muehlmann, A. (International Academy of the Environment, 1998)
This background paper summaries the issues raised by the Kyoto Protocol as background information for discussion aimed at assessing whether joint implementation (JI) and the clean development mechanism (CDM) are opportunities for forest sustainable management through carbon sequestration projects. A synthesis of the results of the discussions will be used : - to provide policy-makers with information that will enable them to elaborate the modalities of these instruments and take well-informed decisions whether they should engage into, or encourage, JI or CDM activities in the forestry sector - to identify gaps in knowledge and researchable issues that will permit a better understanding of the socio-economic, cultural, political, scientific, technical and environmental implications of carbon sequestration, taking into account national and global needs for sustainable development; and - to enhance public awareness and facilitate the understanding whether JI or CDM are opportunities for carbon sequestration projects in the forestry sector The first section lists a number of issues derived from Articles 6 and 1 of the Kyoto Protocol, with some emphasis on foresty sector issues. These issues re then discussed in the subsequent section under (i) methodological issuess including measurement, verification and certification of climate benefits in the forestry sector; (ii) eligibility criteria for JI and CDM projects; (iii) environmental and financial additionality; and (iv) incentives for participating in JI or CDM projects including sustainable development achievement and cost-effectiveness in implementing emissions reductions. Finally, the paper provides some guidance on broad issues that will be considered at the Policy Dialogue.